Analisis Faktor-Faktor Yang Memengaruhi Ekspor Tembakau Di Kabupaten Jember - Adilah Ayu Maulidiyah; Darsono Darsono (Program Studi Magister Agribisnis, Universitas Sebelas Maret, 2023)
The role of tobacco in economic conditions in Indonesia is very large considering the amount of excise tax applied as state revenue. The higher the production and export of tobacco, the higher the state revenue. The study aims to explain the influence of domestic tobacco price factors, tobacco export prices, tobacco production, rupiah exchange rate, real Gross Domestic Product (GDP), and tobacco product excise on the volume of tobacco exports in Jember Regency. This type of research is descriptive research with a quantitative approach. The research uses monthly time series secondary data from 2019 to 2021. The data is analyzed using multiple linear regression analysis with the IBM SPSS Statistics 25 software program. The results of the research show domestic tobacco prices, tobacco export prices, tobacco production, rupiah exchange rate, real GDP, and excise on tobacco products together have a significant effect on the volume of tobacco exports in Jember Regency. The partial test shows that domestic prices and tobacco export prices influence the volume of tobacco exports. These two variables are influential because price decreases and increases will always be related to the level of demand which will also affect export volume.